(untitled) (International Journal of Environmental Sciences, 2025)
This research explores the impact of French Cinema in language acquisition by students learning French as a foreign language. The research investigates how exposure to French cinema influences students’ perceptions, behaviours, and BICS (Basic Interpersonal Communicative Skills) self-identification within the broader socio-cultural dimension and its role in attaining the sustainable development goals for better future. Many people worldwide do not speak French as their first language and have been attempting to acquire it. But the learners of French as a foreign language have very limited and outdated materials in the natural language learning environment, thus, they face difficulty and have to make more efforts while learning French language. Thus, the inclusion of French Cinema in the classes of learning of french as a foreign language offers a real-life situations which is full of dialogues of the day to day life. It is valuable and innovative pedagogical tool as it helps to enhance the language skills in the French language and understand the various issues of United Nations sustainable development goals. Therefore, in the majority of French language classrooms, French teachers have been offering films to language learners in order to increase exposure to the French language and its culture. In fact, when French language is taught utilising authentic material in the form of French films, the students have a unique opportunity to immerse themselves in an authentic setting. This article mainly focuses on the impact of French movies while learning French as a foreign language. It also talks about the methodology of using audio-visual approaches and using French films for the learners of French as a foreign language. The use of these audiovisual tools for teaching and learning French as a foreign language provides an interactive approach to enhance the language skills of the learners while engaging them with the real-world sustainability issues. Moreover, it focuses on the various sustainable development goals (SDGs), particularly cultural adaptation, hybridity, and linguistic identity help to understand the complex relationship between media consumption and language acquisition that leads to the quality education (SDG4).